La identidad cultural y la conciencia turística de los pobladores del distrito de Tambogrande, 2023. - Ávila Navarro, Shirly Margot (2024)
The main objective of this research was to determine the relationship between cultural identity and tourist awareness of residents of Tambo Grande district, research carried out during 2023. The research was basic with a non-experimental, transversal and simple correlational design and a quantitative approach. The sample was represented by 203 residents and the sampling was probabilistic by clusters, to whom a questionnaire on a Likert scale was applied. It was hypothesized that cultural identity is significantly related to the tourism awareness of residents of Tambo Grande district. The results shows that 40% of the residents rated cultural identity at a medium level and 39% rated tourist awareness at a high level. Likewise, cultural identity is significantly related to tourist awareness of residents of Tambo Grande district, which was represented by the Rho coefficient equal to .998** and a p-value equal to 0.000b.